(untitled) (Research, Society and Development, 2021)
The article aims to analyze the perception of the professional about the impact of his performance in the care of users admitted to a hospital specialized in psychiatry. Qualitative ethnographic research where, as a professional of the place in question, I was able to act as a participating observer, using a field diary (totaling 80h) and conducting 25 semi-structured interviews until theoretical saturation with professionals from the infirmary team in order to capture the institutional discourse plan and the contradictions existing in the different perceptions about care in this institution. The results of this research showed that the care provided by the medical professional is still centered on modern scientific rationality, biomedicine and biopower. Care is still focused on resolvability and the notion of “cure” produces professional malaise as the chronification shows itself as a failure of therapeutic efforts. An interdisciplinary team is lacking to build another form of care, the old pair of hospices, nurses and doctors still numerically remains. There are professionals whose work is guided by the logic of psychosocial care, although hampered by the configuration of work processes and the rigidity of routines. The search for a new practice in the clinic, allows a broader understanding of the experience of those who suffer. In this sense, reflecting on what guides this new care and this new clinic puts us in a place of constant search and understanding.